Development of the PLANEA Independent Life Skills Scale for University Students - Hajarani, Sabirina; Vingkan, Rezina; Silvia, Mona; Ananda, Fasya; Haidar, Alfi; Ihsan, Helli; Zaleha, Diah; Ummul, Ghinaya (Jurnal Psikologi Terapan, 2024)
Entering the phase of adulthood requires gradual independence and preparation. College students, as early adults, are expected to take on responsibilities, become more independent, build intimate relationships, enhance friendship commitments, and tackle challenges without relying on their parents. However, many students still lack mental readiness due to a lack of independence. Therefore, this research aims to develop the PLANE independent life skills measurement tool, which can assess the level of independence among college students in managing their lives autonomously. The participants were 212 students, comprising 71.2% females and 28.8% males, with an average age of 19.84 years (SD = 1.26). The research employed a quantitative method, testing person fit and item fit using the Winstep application and Jeffreys Amazing Statistics Program (JASP). Confirmatory Factor Analysis (CFA) and Exploratory Factor Analysis (EFA). Based on the research findings, the instrument demonstrated high reliability (Î± = 0.73), making it suitable for use, and high validity (p > 0.3), indicating the instrument's appropriate construct.